Pengaruh Penambahan Pasir dan Semen Terhadap Kuat Tekan Paving Block Material Tanah Menggunakan Alat Pemadat Modifikasi - Idharmahadi Adha; Setyanto Setyanto; Annisa Wulansari (UNIVERSITAS LAMPUNG, 2016)
Paving blocks made from mixture of portland cement or other hydrolysis adhesive, water, and ag- gregates with or without other materials. In this study, paving blocks are made by using a mixture of soil, portland cement and sand. In the manufacture of paving blocks used compactor modifica- tion that are expected to increase the strength of paving blocks that according to SNI 03-0691- 1996. Soil samples tested were from Kota Baru, South Lampung. The variation of mixture that used in this study is by adding sand as much as 2%, 4%, 6%, 8%, and 10% and add cement as much as 3%, 6%, 9%, 12%, dan 15% as well as with the treatment of pre-combustion and post- combustion of the sample of paving blocks. Results of testing the compressive strength of the paving blocks with a mixture of soil , cement and sand has meet the standard of SNI 03-0691-1996 for the classification of paving blocks quality D which can be used for garden. The combustion process of paving blocks is giving only slightly against the increase in paving blocks without the process of combustion. The highest compressive strength value generated by post-combustion of paving blocks on the variation of mixture 10 % sand + 15 % cement + 75 % soil amounted to 10.05 MPa . While the value of the water absorp- tion test ranged from 16.6 % - 23.8 % so it does not meet the standard of SNI 03-0691-1996 .